Characterization of capsaicinoids and their analogues using feature-based molecular networking analysis - Jang, Hyemi; Choi, Mira; Jang, Kyoung-Soon (Biotechnology and bioprocess engineering, 2025)
Capsaicinoids, a class of alkaloid compounds commonly found in Capsicum annuum, are known for their pungent properties. Recent studies have highlighted metabolites similar in structure and biological activities to known capsaicinoids but lacking the characteristic pungent stimuli. In this study, capsaicinoid-like compounds were investigated from untargeted tandem mass spectrometry (MS/MS) datasets of the ethanolic extracts of Korean local cultivars of red pepper (Subicho and Eumseong) and a phytophthora disease-resistance cultivar (Dokbulwang), obtained using hybrid trapped ion mobility quadrupole time-of-flight mass spectrometry. Feature-based molecular networking (FBMN) in the Global Natural Products Social molecular networking platform, along with an unsupervised substructure identification tool MS/MS Latent Dirichlet Allocation, was employed to characterize capsaicinoid-like clusters. Additionally, the Network Annotation Propagation, an in silico fragmentation tool, complemented the FBMN results. This analysis identified 82 novel capsaicinoid analogues, significantly improving annotation coverage from 6.1% to 24.4%, based on spectral library matching and collision cross-section (CCS) values. The study revealed distinct clusters of capsaicinoid-like compounds, including long-chain N -vanillyl-acylamides such as N -vanillyl-decanamide and zucapsaicin. These compounds were characterized by unique fragmentation patterns, CCS values, and retention times, indicating their structural similarities and differences with known capsaicinoids. The elucidation of these capsaicinoid analogues and their distribution in Korean red pepper cultivars enhances our understanding of the pungency of spices. This research contributes valuable insights into the diversity of capsaicinoid-like compounds, shedding light on their potential applications in various fields such as food science, pharmacology, and agriculture.